Diallel analysis of kernel weight and grain-filling traits in maize grown under contrasting nitrogen supply - Hisse, Ignacio R.; D’Andrea, Karina Elizabeth; Otegui, María Elena (Wiley, 2023)
Understanding the inheritance of maize (Zea mays L.) kernel weight (KW) under contrasting nitrogen (N) supply is crucial for obtaining high KW across diverse N conditions. This work evaluated broad-sense heritability (H2), general combining ability (GCA), and specific combining ability (SCA) under contrasting N levels for (i) KW and kernel number per plant and (ii) grain-filling traits represented by the duration of lag and effective filling phases, kernel growth and desiccation rates, maximum water content and volume, and moisture content at physiological maturity. A six-parent full diallel cross generated via Griffing's method 3 was tested under high (N200) and low (N0) N supply in 2 years (Y). For the various traits: (i) F1 hybrid, and F1 by Y and/or N interactions were significant (p < 0.05); (ii) GCA was significant at both N levels and affected (p < 0.05) by the Y effect; (iii) SCA was important (p < 0.05) only at N200; and (iv) GCA sum of squares was higher than those of SCA (except for KW). For KW and grain-filling traits, H2 and GCA/SCA ratios were higher at N0 than at N200, suggesting low-N environments would be more advantageous for developing genetic selection. Lag-phase duration (LPD), kernel desiccation rate (KDR), and kernel maximum water content (KWCMAX) had higher H2 (≥0.70) and GCA/SCA ratio than KW, particularly under N0. Thus, the highest KW hybrid (LP2×LP662) was composed of inbreds with high GCA for LPD, KDR and KWCMAX, revealing superior KW hybrids could be selected from the GCA of mentioned traits.